Prospective association between maternal allostatic load during pregnancy and child mitochondrial content and bioenergetic capacity. (October 2022) - Gyllenhammer, L.E.; Picard, M.; McGill, M.A.; Boyle, K.E.; Vawter, M.P.; Rasmussen, J.M.; Buss, C.; Entringer, S.; Wadhwa, P.D.
Abstract: Background: Mitochondria are multifunctional energy-producing and signaling organelles that support life and contribute to stress adaptation. There is a growing understanding of the dynamic relationship between stress exposure and mitochondrial biology; however, the influence of stress on key domains of mitochondrial biology during early-life, particularly the earliest phases of intra-uterine/prenatal period remains largely unknown. Thus, the goal of this study was to examine the impact of fetal exposure to stress (modeled as the biological construct allostatic load) upon mitochondrial biology in early childhood. Methods: In n = 30 children (range: 3.5–6 years, 53% male), we quantified mitochondrial content via citrate synthase (CS) activity and mtDNA copy number (mtDNAcn), and measured mitochondrial bioenergetic capacity via respiratory chain enzyme activities (complexes I (CI), II (CII), and IV (CIV)) in platelet-depleted peripheral blood mononuclear cells (PBMCs). In a cohort of healthy pregnant women, maternal allostatic load was operationalized as a latent variable (sum of z-scores) representing an aggregation of early-, mid- and late-gestation measures of neuroendocrine (cortisol), immune (interleukin-6, C-reactive protein), metabolic (homeostasis model assessment of insulin resistance, free fatty acids), and cardiovascular (aggregate systolic and diastolic blood pressure) systems, as well as an anthropometric indicator (pre-pregnancy body mass index [BMI]). Results: An interquartile increase in maternal allostatic load during pregnancy was associated with higher mitochondrial content (24% and 15% higher CS and mtDNAcn), and a higher mitochondrial bioenergetic capacity (16%, 23%, and 25% higher CI, CII and CIV enzymatic activities) in child leukocytes. The positive association between maternal allostatic load during pregnancy and child mitochondrial content and bioenergetic capacity remained significant after accounting for the effects of key pre- and post-natal maternal and child covariates (p's < 0.05, except CI p = 0.073). Conclusion: We report evidence that prenatal biological stress exposure, modeled as allostatic load, was associated with elevated child mitochondrial content and bioenergetic capacity in early childhood. This higher mitochondrial content and bioenergetic capacity (per leukocyte) may reflect increased energetic demands at the immune or organism level, and thus contribute to wear-and-tear and pathophysiology, and/or programmed pro-inflammatory phenotypes. These findings provide potential mechanistic insight into the cellular processes underlying developmental programming, and support the potential role that changes in mitochondrial content and bioenergetic functional capacity may play in altering life-long susceptibility for health and disease. Highlights: Intrauterine stress exposure is associated with childhood mitochondrial biology. Stress relates to higher leukocyte mitochondrial content and bioenergetic capacity. Extends the targets of fetal programming to include the mitochondria. Higher mitochondrial activity may contribute to wear-and-tear and pathophysiology.